2016
DOI: 10.5897/ajpp2015.4444
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oil of Cordia globosa

Abstract: Cordia globosa is used to treat gastrointestinal diseases in San Rafael Coxcatlan, Puebla, Mexico; however, its medicinal properties have not been investigated. This study reports the chemical composition and the antimicrobial effect of C. globosa essential oil. The essential oil of aerial parts was obtained by steam distillation and 25 compounds were identified by gas chromatography-mass spectrometry (GC-MS). The major constituent was α-pinene (38.4%). Antimicrobial activities were tested on 6 bacterial and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The antimicrobial activity of most terpenoids, such as p-cymene, is related to their functional groups, and the hydroxyl group of the phenolic terpenoids and the presence of delocalized electrons are essential elements for their antimicrobial action (NAZZARO et al 2013). Melissa et al (2016) studied the essential oil of C. globosa, collected in Mexico concerning the MIC value against S. aureus, a matter of 1.00 mg/mL was also observed in our study. It is observed that the variation and the synergy of the chemical composition presented in the chemical analyzes of the constituents present, can interfere with the final result (BAKKALI et al, 2008).…”
Section: Mic and Mbc Tests For Essential Oilssupporting
confidence: 65%
See 1 more Smart Citation
“…The antimicrobial activity of most terpenoids, such as p-cymene, is related to their functional groups, and the hydroxyl group of the phenolic terpenoids and the presence of delocalized electrons are essential elements for their antimicrobial action (NAZZARO et al 2013). Melissa et al (2016) studied the essential oil of C. globosa, collected in Mexico concerning the MIC value against S. aureus, a matter of 1.00 mg/mL was also observed in our study. It is observed that the variation and the synergy of the chemical composition presented in the chemical analyzes of the constituents present, can interfere with the final result (BAKKALI et al, 2008).…”
Section: Mic and Mbc Tests For Essential Oilssupporting
confidence: 65%
“…A total of 47 compounds were detected, of which Monoterpenes 17.74%, Monoterpenes oxygenate 6.84%, Sesquiterpenes 40.50%, Sesquiterpenes oxygenate 29.87%. Caryophyllene oxide 13.04%, β-Elemene 12.30 %, and E-Caryophyllene 10.13%.The result was different from some studies found in the literature Melissa et al, 2016. analyzed the essential oil of C. globosa in Mexico and observed it as a major component of the α-Pinene with 38.4%.de Oliveira et al, 2007 analyzed the essential oil of C. globosa and detected it as a major component β-Caryophyllene 39% and caryophyllene oxide 5.9% with total sesquiterpenes of 84.2%.…”
contrasting
confidence: 70%
“…Within the Cordia genus , there is a certain variation in the predominance of certain components of essential oils. Some species mainly contain monoterpene hydrocarbons common to C. cylindrostachia [ 50 ], C. globosa [ 51 ]; some sesquiterpene hydrocarbons, as seen in C. verbenacea [ 6 ], C. leucocephala [ 52 ] and C. millenii [ 53 ]; a mixture of monoterpene hydrocarbons and sesquiterpenes prominent in C. trichotoma [ 54 ] and C. multispicata [ 55 ]; oils containing oxygenated monoterpenes/sesquiterpenes, such as C. myxa [ 56 ] and C. chacoensis [ 57 ], respectively; and oils with a high content of non-terpenes, present in C. sebestena [ 58 ] and C. gilletii [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varronia globosa (Boraginaceae), a shrub that grows in tropical areas of America, is a medicinal plant that is traditionally used for the treatment of diverse illnesses [ 19 ]. Various biological activities have been reported for V. globosa, such as antibacterial and antifungal properties [ 20 ], as well as larvicidal activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%